Recurrent Inverted Papilloma: Diagnosis with Pharmacokinetic Dynamic Gadolinium-EnhancedMR Imaging - Lai, Ping H.; Yang, Chien F.; Pan, Huay B.; Wu, Ming T.; Chu, Sau T.; Ger, Luo P.; Huang, Wen C.; Hsu, Cheng C.; Lee, Chung N. (American Journal of Neuroradiology, 1999)
BACKGROUND AND PURPOSE: Dynamic gadolinium-enhanced MR imaging has been used successfully to identify post-treatment recurrence or postoperative changes in rectal and cervical carcinoma. Our purpose was to evaluate the usefulness of dynamic gadolinium-enhanced MR imaging for distinguishing recurrent inverted papilloma (IP) from postoperative changes.METHODS: Fifteen patients with 20 pathologically proved lesions (recurrent IP, 12; fibrosis or granulation tissue, eight) were enrolled in the study. Three observers, blinded to pathologic results, independently evaluated conventional MR images, including T1-weighted (unenhanced and postcontrast), proton-density–weighted, and T2-weighted spin-echo images. Results then were determined by consensus. Dynamic images were obtained using fast spin-echo sequences at 5, 30, 60, 90, 120, 150, 180, and 300 seconds after the injection of gadolinium-diethylenetriamine penta-acetic acid. Time-signal intensity curves of suspected lesions were analyzed by a pharmacokinetic model. The calculated amplitude and tissue distribution time were used to characterize tissue, and their values were displayed as a color-coded overlay.RESULTS: T2-weighted images yielded a sensitivity of 67%, a specificity of 75%, and an accuracy of 70% in the diagnosis of recurrent IP. Contrast-enhanced T1-weighted images yielded a sensitivity of 75%, a specificity of 50%, and an accuracy of 65%. Pharmacokinetic analysis showed that recurrent IP had faster (distribution time, 41 versus 88 seconds) and higher (amplitude, 2.4 versus 1.2 arbitrary units) enhancement than did fibrosis or granulation tissue. A cut-off of 65 seconds for distribution time and 1.6 units for amplitude yielded a sensitivity of 100% and a specificity of 100% for diagnosing recurrent IP.CONCLUSION: Dynamic MR imaging can differentiate accurately recurrent IP from postoperative changes and seems to be a valuable diagnostic tool.